Kontribusi Pendidikan Islam dalam Menumbuhkan Kecerdasan Emosional - Nisa, Alifia Wahyuni Choirun; Susandi, Ari (Fakultas Tarbiyah dan Ilmu Tarbiyah, Universitas PTIQ Jakarta, 2021)
Emotional intelligence is an educational concept that has not been widely noticed by educators in the world of education. In general, the world of education is dominated by the concept of intellectual intelligence that includes theory and practice. In relation to Islamic education, emotional intelligence has a significant influence to realize individuals who are knowledgeable and noble in accordance with the characteristics of Islamic teachings. This research aims to examine the contribution of Islamic education in fostering emotional intelligence which includes the concept of emotional intelligence according to the Islamic point of view as well as the strategy and implementation of Islamic education in fostering emotional intelligence. This research uses library research method, which is a research method that is done by studying several media or scientific facilities such as books, scientific papers, journals, and articles to solve a particular problem. The problems studied in this study include how the concept of emotional intelligence according to the Islamic point of view and how the strategy and implementation of Islamic education in fostering emotional intelligence. The results of this study are describing the concept of emotional intelligence according to the Islamic point of view, outlining Islamic education strategies in fostering emotional intelligence and explaining the implementation of Islamic education in fostering emotional intelligence.